2019
DOI: 10.4081/dr.2019.8265
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD27 and MIF as possible serum biomarkers of vitiligo activity in Egyptian patients in Sharkia Governorate

Abstract: Contrary to other inflammatory skin disorders like psoriasis or atopic dermatitis, vitiligo does not present with distinct inflammatory symptoms that can be easily evaluated by clinical examination. Identification of a putative biomarker to inform early and accurate treatment responses could be of considerable value. This study aims to validate levels of serum soluble CD27 (sCD27) and macrophage Migration Inhibitory Factor (MIF) as biomarkers of vitiligo to improve the quality of disease management. This cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…This expression correlated with the hypo or demethylation of the CD70 gene promoter area, which causes a failure to repress CD70 expression when it is triggered by T cell activation [ 15 , 16 ]. Regarding CD27, its soluble serum level was elevated in patients with active vitiligo and was suggested as a marker of disease progression [ 17 , 18 ]. Serum soluble CD27 was downregulated upon treatment of psoriasis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This expression correlated with the hypo or demethylation of the CD70 gene promoter area, which causes a failure to repress CD70 expression when it is triggered by T cell activation [ 15 , 16 ]. Regarding CD27, its soluble serum level was elevated in patients with active vitiligo and was suggested as a marker of disease progression [ 17 , 18 ]. Serum soluble CD27 was downregulated upon treatment of psoriasis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another report that studied GITR family-related receptor on CD8 T cells confirmed that this can induce protective and high-avidity T cell responses as GITR stimulation-induced very weak CD8 T cell responses to melanocyte differentiation antigens expressed by the tumor and did not induce autoimmune vitiligo [52]. Many of these molecules were described as inhibitory elements for T cells, and so many investigators used their blocking factors during the management of tumors like melanoma to release the cytotoxic lymphocytes against the targeted tumor cells [9,37,50].…”
Section: Lymphocytes In Melanomamentioning
confidence: 96%
“…They are related to the innate immunity track and may confirm the need for this arm of action to activate the anergic clones. There is evidence that these markers have a capacity to indicate the probability of future disease progression [9,37]. These factors may ensure lymphocyte survival, T-cell proliferation, and memory cell formation and their expression supported helper Th1 development.…”
Section: • Melanocytes Harboring Shared Antigenicmentioning
confidence: 99%
“…Vitiligo biomarkers, characterizing active vitiligo status early on and in the absence of clinical signs of the pathology, have been previously identi ed [31]. They include an augmented presence in patient circulation of in ammatory molecules such as the chemokine (C-X-C motif) ligand (CXCL)9/MIG [32][33][34], CXCL10/IP-10 [32,35,36], and CXCL11/I-TAC [36], S100B [37,38], IL-17A [39,40], soluble forms of CD25/IL-2 receptor alpha (IL-2 Rα) [41][42][43] and CD27/TNFRSF7 [43,44]. Moreover, some microRNAs (miRNAs), such as miR-16, miR-19b, and miR-25, were highly expressed in vitiligo patients, while miR-574 was downregulated, compared with healthy controls [45][46][47].…”
Section: Introductionmentioning
confidence: 99%